Pengaruh Motivasi Kerja Dan Kepemimpinan Visioner Terhadap Efektivitas Kerja Guru SD - Rina, Rina; Kurniatun, Taufani C.; Safa’at, Ajat (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THE INFLUENCE OF WORK MOTIVATION AND VISIONARY LEADERSHIP ON ELEMENTARY TEACHERS' WORK EFFECTIVENESSWith its practical implications, this study aims to identify strategies that can enhance teacher work effectiveness by examining its association with work motivation and visionary leadership. The study was conducted on a population of 140 civil servant teachers, with a sample of 104 teachers, determined using the Yamane formula with a 5% error tolerance. Data were collected through a questionnaire instrument and analyzed using descriptive and inferential statistical methods. The findings of the study revealed three crucial and positive relationships. First, a strong and positive correlation was found between work motivation and teacher work effectiveness (correlation coefficient of 0.63). Second, a positive and significant relationship was observed between visionary leadership and teacher work effectiveness (correlation coefficient of 0.48). Third, a positive and significant relationship was identified between work motivation, visionary leadership, and teacher work effectiveness (correlation coefficient of 0.696)...